The effects of a pre- and post-exercise whey protein supplement on protein metabolism and muscular strength among elite wrestlers - Sharawy, A. (Science, Movement & Health, 2013)
Whey protein is a high-quality dairy protein that contains all the amino acids the body requires for muscle protein synthesis. Evidence suggests that whey protein, found naturally in milk, increases muscle protein synthesis that in combination with resistance exercise can improve body composition. The aim of this study was to determine the effects of a pre- and post-exercise whey protein supplement on protein metabolism and muscular strength among elite wrestlers. Methods. Eighteen male wrestlers volunteered to participate in this study. Subjects were randomly divided into supplement pre -exercise (S1; n = 10, 21.3 ± 2.9 y, 175.7 ± 4.9 cm, 86.7± 9.8 kg) or supplement post -exercise (S2; n = 8, 20.8 ± 2.03 y, 172.6 ± 5.7 cm, 85.3± 7.9 kg). subjects were tested for maximal strength (1-RM) on the squat , chest and arm exercises. S1and S2were consumed the whey protein (optimum) 1.4 g/kg.bw/day supplements after immediately following of training session for S1 group and 40 minutes prior to training session for S2 group, all subjects for a period of twelve week, three days weekly. Results. There was a significant difference between the two experimental Groups (S1 and S2) in total protein, albumin, urine and Creatinine and muscular strength for S2 group. Conclusions. The best way to supplement the whey protein was immediately following the training workout.